Measurement of neutron flux and gamma dose rate distribution inside a water phantom for Boron Neutron Capture Therapy study at Dalat Research Reactor - Trinh, Thi Tu Anh; Pham, Dang Quyet; Mai, Nguyen Trong Nhan; Pham, Ngoc Son (Penerbit Universiti Kebangsaan Malaysia, 2019)
Exposure dose rate to the tumor and surrounding cells during neutron beam irradiation in Boron Neutron Capture Therapy (BNCT) comes not only from heavy charged particles produced from the 10B(n,α)7Li nuclear reaction, but also from neutron-induced reactions with other biological elements in living tissue, as well as from gamma rays leaked from the reactor core. At Dalat Research Reactor, Vietnam, the neutron and gamma dose rate distribution inside a water phantom were measured by using activation method and Thermoluminescent Dosimeter (TLD) detector, respectively. The results showed that effective thermal neutron dose rate along the center line of the water phantom had a maximum value of 479 mSv h-1 at 1 cm in phantom and then decreases rapidly to 4.87 mSv h-1 at 10 cm. The gamma dose rate along the center line of the water phantom also reach its maximum of 4.31 mSv h-1 at 1 cm depth and decreases to 1.16 mSv h-1 at 10 cm position. The maximum biological tumor dose rate was 1.74 Gy-eq h-1, not high enough to satisfy the treatment requirement of brain tumors. However, the results of this work are important in supporting of BNCT study in the upcoming stages at Dalat Research Reactor.